열간압연 공정 조건이 열간압연된 Al-Zn-Mg-Cu-Sc-Zr 합금의 미세조직과 기계적 특성에 미치는 영향 - 정민경; Minkyung Jeong; 조수연; Suyeon Jo; 이동길; Donggil Lee; 육승우; Seungwoo Yuk; 이태호; Taeho Lee; 이수열; Soo Yeol Lee; et al. (대한금속·재료학회지, 62(8), 2024)
7xxx series aluminum alloys possess extremely high cold working yield strength, which make hot working processes essential for component manufacturing. Preheating specimens before or between hot rolling processes significantly affects the mechanical properties of the hot rolled Al alloy sheets, depending on the preheating temperature and time. In this study, we investigated the effects of temperature and time variations in intermediate preheating treatments on the microstructure and mechanical properties of Al-Zn- Mg-Cu-Sc-Zr alloy sheets after hot rolling. Specimens preheated at various temperatures (300, 350, 400℃) after hot rolling showed an increase in hardness with increasing heat treatment time, reaching a peak value before decreasing. Additionally, as the preheating temperature increased, the time to reach the peak hardness decreased. The increase in preheating temperature resulted in an increase in hardness, attributed to the promotion of grain refinement due to recrystallization occurring during hot rolling or subsequent intermediate preheating. When the intermediate preheating time was increased from 15 min to 25 min, the yield strength decreased due to the Orowan mechanism, which resulted from the increase in the size of precipitates and the decrease in their number density. The specimen that underwent heat treatment for 20 min exhibited the highest tensile strength, which was attributed to grain refinement through recrystallization and an increased work hardening rate due to the Orowan mechanism.